2020
DOI: 10.1097/j.jcrs.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of intravitreal triamcinolone–moxifloxacin during cataract surgery on central macular edema in patients with preexisting diabetic retinopathy

Abstract: Purpose: To evaluate the effect of intravitreal triamcinolone acetonide–moxifloxacin at the time of cataract surgery on central macular edema in patients with preexisting diabetic retinopathy. Setting: Loma Linda University Eye Institute, California, USA. Design: Retrospective observational clinical study. Methods: Retrospective chart review included 75 eyes of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In an observational clinical study carried out by Angkadjaja et al , Tri-Moxi was injected after phacoemulsification for patients with preexisting diabetic retinopathy. They have found that this drug was effective in a short term – CMT decreased when measured 4 weeks after the cataract surgery but mean CMT 6–12 weeks postoperatively for 34 eyes increased with a mean increase of 26 μm ( P = 0.021) [114].…”
Section: Management Of Inflammation With the Dropless Cataract Surgerymentioning
confidence: 99%
“…In an observational clinical study carried out by Angkadjaja et al , Tri-Moxi was injected after phacoemulsification for patients with preexisting diabetic retinopathy. They have found that this drug was effective in a short term – CMT decreased when measured 4 weeks after the cataract surgery but mean CMT 6–12 weeks postoperatively for 34 eyes increased with a mean increase of 26 μm ( P = 0.021) [114].…”
Section: Management Of Inflammation With the Dropless Cataract Surgerymentioning
confidence: 99%